2010
DOI: 10.1016/j.molcel.2010.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B Phosphorylates Spatially Distinct Targets to Differentially Regulate the Kinetochore-Microtubule Interface

Abstract: Summary Accurate chromosome segregation requires carefully regulated interactions between kinetochores and microtubules, but how plasticity is achieved to correct diverse attachment defects remains unclear. Here, we demonstrate that Aurora B kinase phosphorylates three spatially distinct targets within the conserved outer kinetochore KNL1/Mis12 complex/Ndc80 complex (KMN) network, the key player in kinetochore-microtubule attachments. The combinatorial phosphorylation of the KMN network generates graded levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
629
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(660 citation statements)
references
References 26 publications
23
629
2
6
Order By: Relevance
“…This group further reported that phosphorylation of KNL1 on sites Ser24 and Ser60 by Aurora B kinase negatively regulates PP1 binding to KNL1 as a phosphomimetic version of KNL1 bound to PP1 in vitro with much less affinity than did wild-type KNL1 . A later study demonstrated that KNL1 Ser24 and Ser60 are phosphorylated at kinetochores in vivo in an Aurora-B-kinasedependent manner and, as mentioned above, using phosphorylationspecific antibodies, these authors measured a 30-50% decrease in phosphorylated KNL1 on kinetochores from prometaphase to metaphase (Welburn et al, 2010). Presumably, this reduction of phosphorylation on KNL1 at kinetochores is sufficient to increase the affinity of KNL1 for PP1 so that kinetochore targets can be dephosphorylated.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This group further reported that phosphorylation of KNL1 on sites Ser24 and Ser60 by Aurora B kinase negatively regulates PP1 binding to KNL1 as a phosphomimetic version of KNL1 bound to PP1 in vitro with much less affinity than did wild-type KNL1 . A later study demonstrated that KNL1 Ser24 and Ser60 are phosphorylated at kinetochores in vivo in an Aurora-B-kinasedependent manner and, as mentioned above, using phosphorylationspecific antibodies, these authors measured a 30-50% decrease in phosphorylated KNL1 on kinetochores from prometaphase to metaphase (Welburn et al, 2010). Presumably, this reduction of phosphorylation on KNL1 at kinetochores is sufficient to increase the affinity of KNL1 for PP1 so that kinetochore targets can be dephosphorylated.…”
Section: Discussionmentioning
confidence: 79%
“…Based on the findings that Hec1 N-terminal phosphorylation is significantly reduced after chromosome bi-orientation, it is probable that other mechanisms for inducing kinetochore-MT detachment and error correction are in place during late mitosis (Bakhoum et al, 2009). Recently, it has been demonstrated that both KNL1 and DSN1 (a member of the Mis12 complex) are phosphorylated in an Aurora-B-kinase-dependent manner in vivo, and phosphorylation of these proteins results in decreased affinity of the KMN complex for MTs in vitro (Welburn et al, 2010). Phosphorylated forms of both KNL1 and DSN1 at kinetochores decrease only modestly from prometaphase to metaphase (~33-55% reduction for KNL1-P and ~20% reduction for DSN1-P), thus it is possible that phosphorylation of these members of the KMN complex by Aurora B in late mitosis is sufficient to induce some level of kinetochore-MT turnover even in the absence of high levels of Hec1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal tail is unstructured and not present in the crystal structure of Ndc80 complexes or in cryo-electron microscopy images of the Ndc80 complex bound to MTs. The N-terminal tail of Ndc80 is enriched for Ipl1/AuroraB phosphorylation sites, and MT binding can be regulated by the kinase (Guimaraes et al 2008;Welburn et al 2010;Lampson and Cheeseman 2011;. MT-binding affinity of yeast and human Ndc80 complexes is decreased when the Ndc80 N-terminal tail is deleted (Wei et al 2005;Ciferri et al 2008).…”
mentioning
confidence: 99%
“…This protein kinase, which is located at the centromeres between the two sister-kinetochores, plays an essential role in the correction of erroneous kinetochore-microtubule attachment Nezi and Musacchio 2009). Specifically, it phosphorylates the microtubule-binding KMN network at kinetochores in a proximity-dependent manner if kinetochores are not stretched apart through a bipolar attachment Welburn et al 2010). But it has also been implicated directly in the spindle checkpoint signaling, as it contributes to the loading of Mad2 to kinetochores in human cells and is essential for the spindle checkpoint in S. pombe (Johnson et al 2004;Vanoosthuyse and Hardwick 2009).…”
Section: Is It Only Checking Kinetochore-microtubulementioning
confidence: 99%